Värphöns : påverkar de ekonomin på växtodlingen - Bergström, Johan; Johansson, Martin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
In this degree project we wanted to investigate if there are any possibilities to get a higher income from grain growing by giving the grain to hens instead of selling it. We were also wondering if the manure has any value or if it only cost the egg producer money. If the egg producer cultivate his own grain and is able to store it in layer is there quite much money to earn. Expensive pasture makes it profitability to pay up to 1,35 Swedish crowns for a kilo of wheat. In our calculating we've used calculation from the company Lantmännen. This high price for grain opens also the possibility to make a deal with any neighbour if the egg producer is unable to grow his own grain. From a hen house that holds 20 000 hens comes about 1100 cubic meters of manure a year. This little quantity doesn't carry the costs of an expensive dung spreader. Financial the egg producer shall hire that service. It is difficult to decide the manure value. It depends on which fertilizer you compare with. In this degree project we have compared the manure with three different fertilizers. We have also interviewed five egg producers that value the manure different.